Torah centers and rabbinic activity in Palestine, 70-400 CE : history and geographic distribution - Rozenfeld, Ben Tsiyon. (Supplements to the Journal for the Study of Judaism, 2010)
This book analyses the data about Torah centers and rabbinic activity in Palestine during Mishnaic and Talmudic times, 70-400 CE-the Roman and early Byzantine periods. The research is an interdisciplinary inquiry. It encompasses rabbinic literature as well as archeology, geography, and sociology, thus enriching the discussion of the history and scope of rabbinic activity in the different regions of Palestine. Arranged in chronological order, the book highlights the changes generated by historical events, in particular the relocation of rabbinic centers following the upheaval of the Bar Kokhba Revolt. In spite of this upheaval, Torah centers continued to develop in Palestine for several hundred years, until the end of the period under discussion.